Komponen Hasil dan Karakter Morfologi Penentu Hasil Kedelai pada Lahan Sawah Tadah Hujan - Hakim, Lukman (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2017)
Yield component and morphological characters determining grain yield of soybean on rainfed land after rice cultivation. Twelve soybean varieties were evaluated on rainfed wetland after rice in Grobogan, Central Java, during the late dry season of 2014. The experiment was arranged in randomized block design with four replications. Each of the genotype was grown in five rows of four and half meters long. Plant spacing was 40 cm x 15 cm, each hill contained two plants. Result showed that among the yield components, number of pods per plant, seed size and harvest index were positively correlated with grain yield (r = 0.530; 0.376 and 0.608). The direct effect of pods per plant (x5), seed size (x6) and harvest index (x8) to grain yield as indicated by path coefficient were the highest (x5 = 0.813, x6 = 0.540, x8 = 0.901), while the effect of other yield components were small or negative. Based on both analyses, soybean genotypes with high grain yield should have high number of pods per plant (>40 pods), large seed size (>15 g/100 seeds) and high harvesting index (>50%). Therefore, pods per plant, seed size and harvesting index can be used as selection criteria on rainfed wetland after rice in the late dry season. Although the direct effect of days maturity to grain yield was small, but early maturing varieties should be consider to be used as selection criteria, because on rainfed wetland during the late dry season soil moisture often is uncertain. Therefore, early maturing varieties can be more useful under this condition to minimized yield losses due to drought stress.